Pengaruh Current Ratio Dan Debt Equity Ratio Terhadap Return On Equity Pada Koperasi Warga Komplek Gandaria Periode 2013-2022 - Taufan Saputra; Sari Karmiyati (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the Current Ratio and Debt Equity Ratio affect Return On Equity at the Gandaria Complex Residents' Cooperative. This research method uses a quantitative method and research data in the form of secondary data obtained from financial data at the Gandaria Complex Residents' Cooperative. The population is all financial reports at the Gandaria Complex Residents' Cooperative with the number of samples selected in the period 2013 to 2022 for 10 (ten) years. The analysis used is Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, and Hypothesis Test processed using SPSS 26. The results of the study indicate that the Current Ratio variable does not affect Return On Equity, this is evidenced by a significant value of 0.063> 0.05. The Debt Equity Ratio variable affects Return On Equity, this is evidenced by a significant value of 0.045 <0.05. The Current Ratio and Debt to Equity Ratio variables have an effect on Return On Equity, this is proven by a significant value of 0.030<0.05.